Satellites Scan the Seas - Allan, T. D. (The International Hydrographic Review, 2015)
A brief review of the role played by satellites in the marine sciences up to the present is followed by a more detailed assessment of the significance of adopting micro-wave remote sensors as well as visible and infrared instruments. The sensors carried on Seasat-A — the first satellite entirely devoted to the marine sciences — are described and the potential benefits of the Seasat programme, both to applied and pure research, are considered. These include an improvement in forecasts of wind and wave climate ; monitoring coastal processes ; providing basic data to the study of marine geodesy and ocean tides ; and delineating changing ice patterns in polar regions.